Analysis of Factors Affecting Financial Performance in Local Governments with Community Participation as a Moderating Variable - Yogga Yerriandha; Rindu Rika Gamayuni; Saring Suhendro (LPPPIPublishing, 2026)
This research seeks to provide empirical evidence regarding the influence of local own-source revenue and capital expenditure on the financial performance of local governments, as well as to analyze the moderating role of community participation in these relationships. The study population comprises all regency and municipal governments in Indonesia for the fiscal years 2022–2023. A census (total sampling) approach was employed by utilizing all available observations, yielding 1,016 data points from regency and city governments over the two-year period. The data were sourced from Budget Realization Reports and Operational Reports as presented in the Local Government Financial Statements. The empirical results indicate that local own-source revenue exerts a positive and statistically significant effect on local government financial performance. Likewise, capital expenditure is found to have a positive and significant impact on financial performance. Community participation is shown to significantly weaken the relationship between local own-source revenue and financial performance. Conversely, community participation strengthens the effect of capital expenditure on financial performance; however, this moderating effect is not statistically significant.